Political parties and candidates internal selection process in colombia (2009)
The internal selection of candidates is one of the most important routines of the political parties; contrary to the international literature, in Colombia, the internal life of these organizations is studied very little. The selection instrument is intimately related with the nature of the party and it will have a direct incidence with the discipline of the party members facing the party’s leadership. It is for this reason that the classification set out by the text for the study of the selection processes is determined by the level of concentration of this decision and it is found at the highest level of centralization: when this decision is concentrated in only one person or on a very reduced group of people; and the highest level of decentralization where the party subjects its decision to consultations and allows for the partici pation of all the electoral census citizens.